E-Counseling IKIP Siliwangi sebagai Primadona Pelayanan Pasca Pandemi: (Kajian dalam Perspektif Teknologi Informasi dan Komunikasi Bimbingan & Konseling) (Jurusan Bimbingan dan Konseling Islam, 2021)
During this pandemic, counselors are required to balance their academic competence with the ability to operate the technology used as an intermediary for the implementation of their service process. The demands for competence that must be possessed by a counselor must be based on the needs of the times, not least in the era of massive technology used during the pandemic and its use will be predicted to be needed until after the pandemic period as well. The solution we offer in responding to the challenges of the times is by developing a web-based e-counseling. E-Counseling IKIP Siliwangi is the result of a big idea that was created to break through barriers in psychological problems. The writing methodology in this scientific paper uses literature based/library study-based writing which is carried out by reviewing and exploring various theories and praxis through literature ranging from books, scientific journals, dissertations, e-books, internet and various data and facts that exist in society. Today e-counseling is no longer an experiment that will be developed, but e-counseling is a result of a scientific research whose use is becoming increasingly rapid based on strong scientific arguments.